PKM Pengenalan Pengelolaan Marketplace Kepada Warga Komplek Kebersihan RT 13 RW 10 Cengkareng - Mohamad Firdaus; Aditya Herliawan; Indra Bakti (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
Online marketplace is so mushrooming that it can make it easier for someone to transact in everyday life. By introducing this technology to the community, especially residents of Komp. Kebersihan RT13 / RW10 Cengkareng West Jakarta. It is hoped that it can make it easier for someone to start an online shop business, or make it easier for someone to promote their products, therefore by conducting learning in the context of community service to socialize the introduction of the online marketplace and also provide training on the use of features in the marketplace that can be used by residents of Komp. housing. Kebersihan RT13/RW10 Cengkareng West Jakarta. This is a community service activity by us.